Penerapan Game Tic-Tac-Toe dengan Metode Artificial Neural Network dalam Pengambilan Keputusan untuk Meraih Kemenangan - Faqih, Ahmad Abdullah; Fitrani, Arif Senja (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
Tic-Tac-Toe is a game played by only 2 players using a 3x3 board. The player must alternately fill in the empty places so that they can form a straight line horizontally, vertically or diagonally so that it can be said to have won. The purpose of this study is to reintroduce traditional games to the community and also to conduct computer training to provide intelligence to the tic-tac-toe game and have learning at each different level of difficulty. The methodology used in this research is using the Artificial Neural Network Method which is an attempt to imitate the function of the human brain. The human brain is thought to consist of millions of tiny processing units called neurons that work in parallel. The data used in the application of the Tic-Tac-Toe game using the Artificial Neural Network Method in Decision Making to Achieve Web-based Victory is taken from the Tic-Tac-Toe game which includes game rules, game components and game strategy. In the Tic-Tac-Toe game in making decisions to win, it has an accuracy value of 80% for easy difficulty, 40% for medium difficulty, and 30% for hard difficulty, this shows that for the computer to win the game is quite easy on the hard difficulty level and on the easy difficulty level, the computer is very easy to beat by the user.